Ansel’s pharmaceutical dosage forms and drug delivery systems - Allen, Loyd V. (Wolters Kluwer, 2014)
Ansel’s pharmaceutical dosage forms and drug delivery systems the most comprehensive source on this subject available today! Reflecting the CAPE, APhA, and NAPLEX® competencies, this trusted resource explores the interrelationships between pharmaceutical and biopharmaceutical principles, product design, formulation, manufacture, compounding, and the clinical application of the various dosage forms in patient care, as well as regulations and standards governing the manufacturing and compounding of pharmaceuticals.